Tourism Village Development through Empowerment Approach in Kampung Island Besing, Berau Regency - Ghisa Aulia Rahmah; Siti Nurbayani K; Nindita Fajria Utami (Budapest International Research and Critics University, 2022)
This study aims to examine the ongoing process of community empowerment in the development of a tourist village in Kampung Pulau Besing. This type of research is descriptive with a qualitative approach. This approach is used to describe and analyze community empowerment in the development of Pulau Besing Tourism Village. Data collection techniques through interviews, observation, and documentation. Research informants include the Head of the Village, Head of the Tourism Awareness Group, and one homestay manager. The results of community empowerment through tourism village training in Pulau Besing Village, Berau Regency are 1) Increasing public knowledge about tourism, It is proven by the people of Besing Island who have realized that the tourism potential on Besing Island if managed optimally in mutual cooperation will provide an attraction for tourists to visit and have recreation in this village. So that it can move the village economy, where village income is not only relied on in the fisheries and handicraft sectors. 2) The development of independence and creativity, this is implemented with the community having started branding the Kampung Pulau Besing tourist destination through the Instagram Social Media platform, promotions involving influencers and stakeholders, making posters of attractive tour packages, and often creating published content about tourism activities on Besing Island.